Lizards of the World Natural History and Taxon Accounts - Rodda, Gordon H. (Book collections on Project MUSE., 2020)
"Author Gordon Rodda has created the first comprehensive compilation of the natural history and ecology of all the world's lizards. He presents an alternative taxonomic understanding of lizards that will challenge received wisdom. This unparalleled informational source will be an essential reference work for reptile scientists and students of herpetology"--